ANALISIS BUDAYA DAN ETIKA BISNIS DALAM PEMBENTUKAN MANAJEMEN KINERJA KARYAWAN - Apsari, Phatriakalista Intan; Putri, Isnawati Setyo; Abdillah, Jihan; Zain, Achmad Majdi; Firmansyah, Nahzul Abugy (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
Manufacturing, trading, or service companies have increasingly fierce competition, so based on this fact, a company must have the expertise to manage the company efficiently in order to achieve the planned goals. So one of the things that must be considered by the company is about culture and business ethics. Corporate culture will affect the strength or weakness of the company on performance within a company, as well as ethics. Ethics is needed in any activity, including the business world. This research is the result of qualitative research using library research methodology, which refers to books and scientific works related to business ethics, organizational culture, and corporate culture. The results obtained are that culture contributes to the formation of ethical behavior, because an organizational culture is a combination of values ​​and norms to guide the actions of all company employees. This ethical behavior arises from the rules called business ethics. A strong culture will be a company tool to compete with competitors. Because a strong culture will be able to increase constant behavior, which can create effectiveness within the organization which is certainly influenced by the performance of employees within the company.